2015
DOI: 10.1007/s12540-015-4397-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambient and cryogenic S-N fatigue behavior of Fe15Mn steel and its weld

Abstract: The S-N fatigue behavior of Fe15Mn (Fe-0.7C-15Mn-2Al) austenitic steel, including base metal and butt-welded joint, was investigated at 298 K and 110 K, and the results were compared to those of STS304L (Fe-1Si-2Mn-20Cr-10Ni) counterparts. Both specimens showed improved resistance to S-N fatigue with decreasing temperature from 298 K to 110 K. The resistance to S-N fatigue of Fe15Mn steel was greater at 298 K, while it was lower at 110 K, than STS304L steel. Unlike STS304L, Fe15Mn steel did not show any notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Vitos et al 86 also collected the SFE values of Fe- (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) Cr- (13)(14)(15)(16))Ni (at.-%) steels measured using the TEM and the XRD from the literature, and compared them with the values calculated using ab initio simulation. They found that the addition of Cr to austenitic stainless steels lowers their SFE values.…”
Section: Alloying Elements Decreasing the Sfe (Cr And Si)mentioning
confidence: 99%
See 2 more Smart Citations
“…Vitos et al 86 also collected the SFE values of Fe- (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) Cr- (13)(14)(15)(16))Ni (at.-%) steels measured using the TEM and the XRD from the literature, and compared them with the values calculated using ab initio simulation. They found that the addition of Cr to austenitic stainless steels lowers their SFE values.…”
Section: Alloying Elements Decreasing the Sfe (Cr And Si)mentioning
confidence: 99%
“…The temperature as well as alloying elements is also an important factor for the SFE. Rémy et al 122 gave an overview of a temperature dependence of SFE, which was measured using the TEM, in Fe- (17)(18)(19)(20)Cr- (13)(14)(15)Ni and Fe-20Mn-4Cr-0.5C (wt-%) steels. They reported that the SFE value of Fe-Cr-Ni steels increased by approximately 0.1 mJ m −2 per K when the temperature rose from 300 to 400 K and that those of Fe-Mn-Cr-C steels were arisen by 0.06 mJ m −2 per K with increasing temperature from 300 to 390 K; these results stemmed from the improvement of γ stability with an increase in temperature.…”
Section: Temperature Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that the resistance to HCF in some non-ferrous alloys is largely determined by tensile strength or yield strength [11,[30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] Typically, steel composed of retained austenite with a face-centered cubic (FCC) crystal structure exhibits suitable tensile strength and toughness at room and cryogenic temperatures. [2][3][4][5][6][7] The presence of the FCC crystal structure is essential for achieving low-temperature toughness because of its superior slip system compared to that of other crystal structures, such as body-centered cubic (BCC) and hexagonal close-packed structures. [2][3][4] Furthermore, unlike BCC crystal structures, FCC crystal structures do not exhibit a ductile-brittle transition at low temperatures.…”
mentioning
confidence: 99%